Breastfeeding and cardiometabolic risk factors in adulthood: results from the Pelotas (Brazil) birth cohort, 1982 - Natália Peixoto Lima; Janaína Vieira dos Santos Motta; Bernardo Lessa Horta (Cadernos de Saúde Pública, 2025)
Using data from a birth cohort study, we evaluated the long-term association between breastfeeding and metabolic cardiovascular risk factors at 30 years old. In 1982, the 5,914 live births in maternity hospitals in Pelotas, Rio Grande do Sul State, Brazil, were examined and the mothers were interviewed. Since then, these participants have been prospectively followed. The cohort members were interviewed at 30 years old and information on blood pressure, carotid intima-media thickness, pulse wave velocity, random blood glucose, and blood lipids were obtained. Simple and multiple linear regressions were used. In the crude and adjusted analyses, duration of breastfeeding did not show any clear association with mean arterial pressure, carotid intima-media thickness, and pulse wave velocity. Likewise, total and non-HDL cholesterol and blood glucose were not related to infant feeding. Regarding HDL cholesterol, it was positively related to predominant breastfeeding duration in the crude analysis, but the association disappeared after controlling for confounding variables. Concisely, our findings suggest that there is no association between duration of breastfeeding and cardiometabolic risk factors in adulthood. Despite that, promotion and support of breastfeeding must be reinforced due to its well-known benefits, such as reduction of infant and child mortality and human capital development.